Microbes matter: Unravelling trade-offs between integrated management options and microbial functions - Kihara, Job Maguta; Bolo, Peter Omondi (Bioversity International and the International Center for Tropical Agriculture, 2021)
We start with key highlights. We then present the soils as influenced by management practices followed by influences to overall microbes. Effects on specific functional groups including zinc and phosphorus solubilization follows before a presentation of how these relate with the soil properties. This is followed by a section on enzyme activities and another on specific functional genes and fungal to bacterial ratio. We then present data on CO2 evolution and mineralization of nitrogen and phosphorus. We finish with application of micro-biology through bio-inoculants and then a summary of research gaps.